Anatomical and histochemical investigation of the leaf of Teucrium polium, a pharmaceutical sub-shrub of the Greek phryganic formations - Christodoulakis, N.S.; Kogia, D.; Mavroeidi, D.; Fasseas, C. (Journal of Biological Research, 2010)
Although extensively studied for its pharmaceutical properties, Teucrium polium has yet to disclose its leaf structure and the chemical nature of the accumulated or secreted products. Therefore, light, scanning, and transmission electron microscopy along with histochemical tests were employed to investigate the leaf of this perennial dwarf Mediterranean shrub. Structural characteristics include large cells with cutinized walls, creating cavities of obscured function in contact to a vessel element of the conductive tissue and different types of glandular hairs. A variety of secreted materials was identified by certain histochemical stains within the mesophyll cells and the glandular hairs. A dense indumentum of non-glandular hairs protects the secretory apparatus and the leaf surface from the stressful conditions of the Mediterranean climate.
Keywords: Histochemistry; Leaf anatomy; Secondary metabolites; Secretory structures; Teucrium; Teucrium polium